Influence of Iron Addition (Alone or with Calcium) to Elements Biofortification and Antioxidants in Pholiota nameko - Budzyńska, Sylwia; Siwulski, Marek; Magdziak, Zuzanna; Budka, Anna; Gąsecka, Monika; Kalač, Pavel; Rzymski, Piotr; Niedzielski, Przemysław; Mleczek, Mirosław (Plants (Basel, Switzerland), 2021)
Mushrooms supplementation with iron (Fe) is usually limited, and therefore it would be beneficial to search for other vital elements able to improve the process. The aim of this study was to verify a possible interaction between Fe and calcium (Ca) to estimate the role of the addition of the latter metal to stimulate Fe accumulation in Pholiota nameko. Additionally, an analysis of phenolic compounds and low molecular weight organic acids (LMWOAs) was performed. The increase of Fe concentration in the substrate caused a significantly higher accumulation of this metal in P. nameko. The addition of Ca (5 or 10 mM) stimulated Fe accumulation, just as Fe concentration in the substrate stimulated Ca accumulation, which pointed to a synergism between these metals. The obtained results show that the presence of Fe in the substrate may also promote K, Mg, Mn, Na, P, and S accumulation. In contrast, the addition of Ca stimulates and/or inhibits their content in fruit bodies. The phenolic and organic acids profile was poor. Only gallic, 4-hydroxybenzoic, sinapic and syringic acids (phenolics), as well as citric and succinic acids (LMWOAs), were quantified in some combinations in P. nameko fruiting bodies.
Keywords: iron deficiencies; mushroom supplementation; functional food; metal interaction